2014
DOI: 10.1088/1748-0221/9/03/p03014
|View full text |Cite
|
Sign up to set email alerts
|

GaAs/Al0.8Ga0.2As avalanche photodiodes for soft X-ray spectroscopy

Abstract: The soft X-ray spectroscopic performance of a GaAs/Al 0.8 Ga 0.2 As Separate Absorption and Multiplication (SAM) APD was assessed at room temperature using a 55 Fe source. An energy resolution of 1.08 keV (FWHM) was achieved for the 5.9 keV X-rays, at an avalanche gain of 3.5. The avalanche gain also improved the minimum detectable energy from 4.8 keV at unity gain to about 1.5 keV at a gain of 5. Through avalanche statistics analyses, we confirmed that (i) the APD's FWHM was degraded by X-ray photon absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…The model is then applied to template staircase APDs in Sec.IV to demonstrate that it is consistent with the theory in [12]. Comparison with experimental literature data for heterojunction [4], [5] and staircase APDs [2] is provided in Sec.V. Conclusions are finally drawn in Sec.VI.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…The model is then applied to template staircase APDs in Sec.IV to demonstrate that it is consistent with the theory in [12]. Comparison with experimental literature data for heterojunction [4], [5] and staircase APDs [2] is provided in Sec.V. Conclusions are finally drawn in Sec.VI.…”
Section: Introductionsupporting
confidence: 72%
“…In this section we apply the EBHDM model to two realistic structures: the Separate Absorption and Multiplication (SAM) GaAs/Al 0.8 Ga 0.2 As APD described in [4], [5] (Fig.5a) and the staircase SAM-APD presented in [2] (Fig.5b).…”
Section: Application To Heterojunction Apdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gomes et al have reported a GaAs/Al 0.8 Ga 0.2 As Separate Absorption and Multiplication region Avalanche Photodiode (SAM-APD) with a resolution of 1.08 keV when exposed to 55 Fe source [5]. The effect of avalanche gain improved the resolution.…”
Section: Introductionmentioning
confidence: 99%
“…A GaAs/AlGaAs SAM‐APD comprised of a 4.5 µm absorption region and a staircase‐like multiplication region has been developed for X‐ray photo‐detection . Meanwhile, a similar GaAs/Al 0.8 Ga 0.2 As SAM‐APD structure has been also demonstrated to detect soft X‐rays at 5.9 keV with a full‐width half‐maximum (FWHM) of 1.08 keV . However, its spectroscopic characterizations show an undesired secondary peak located at energy lower than the 5.9 keV peak.…”
Section: Introductionmentioning
confidence: 99%